Student engagement in digitalen Lehr-Lern-Szenarien - Mindt, Ilka; Rebekka, Schmidt (Hochschule auf Abstand. Ein multiperspektivischer Zugang zur digitalen Lehre.)

‘Who’s Going to Mobilise Darkness and Silence?’ The Construction of Dystopian Spaces in Contemporary British Drama - Tönnies, Merle; Sierz, Aleks (Journal of Contemporary Drama in English)

Promoting Critical Thinking in Literary and Cultural Studies - Fakha, Nadja (die hochschullehre)

‘Ja, ja, so schön klingt das Schreckliche’: An Audionarratological Analysis of Andreas Ammer and FM Einheit’s Lost & Found: Das Paradies - Mildorf, Jarmila (Tuning in to the Neo-Avantgarde: Experimental Radio Plays in the Postwar Period)

Book review: Katharina Fürholzer: Das Ethos des Pathographen: Literatur- und medizinethische Dimensionen von Krankenbiographien. Heidelberg 2019. - Mildorf, Jarmila (European Journal of Scandinavian Studies)

Auricularization and Narrative-Epistemic Stance in Louis Nowra’s Echo Point - Mildorf, Jarmila (Audionarratology: Lessons from Radio Drama)

When Sounds Make Stories: Lessons for Narrative Theory from the Study of Radio Drama - Bernaerts, Lars; Mildorf, Jarmila (Audionarratology: Lessons from Radio Drama)

Audionarratology: Lessons from Radio Drama
Keywords: Narratology; Audio Drama

Folklinguistic perceptions of Global Englishes among German learners of English - Meer, Philipp; Hartmann, Johanna; Rumlich, Dominik (European Journal of Applied Linguistics)

Crossraods of Collective Memory. Canadian Memoir at the Junction of lieux and nœuds de mémoire. - Jende, Yvonne Kristin (The Place of Memory and the Memory of Place, International Conference)

Truth Be Told, ... or Not? Reality and Perspective in New Sincerity Memoir. - Jende, Yvonne Kristin (Bridges and Barriers: Perspectives of Progress and Preservation, Interdisciplinary and International Conference)

Bridges and Barriers, Interdisziplinäre studentische Konferenz

Student engagement in digitalen Lehr-Lern-Szenarien - Schmidt, Rebekka; Mindt, Ilka (Hochschule auf Abstand. Ein multiperspektivischer Zugang zur digitalen Lehre)
In diesem Beitrag wird das Konzept des student engagement mit den drei Dimensionen Verhalten, Emotion und Kognition skizziert und in Bezug auf die unterstützenden Faktoren für Lehre auf Distanz in digitalen Lehr-Lernsettings untersucht. Ein Abgleich der theoretischen Grundlagen mit Forschungsergebnissen verschiedener Studien zum Onlinesemester 2020 sowie eine Konkretisierung durch Evaluationen aus Seminaren der englischen Sprachwissenschaft und der Kunstdidaktik gibt Aufschluss darüber, wie ein geeignetes how to engage auch in digitalen Lehr-Lernsettings gelingen kann. Darüber hinaus lassen die Ausführungen erkennen, dass die unterstützenden Faktoren häufig in ähnlich priorisiert werden. Daraus ergibt sich eine Reihenfolge mit dem unterstützenden Umfeld an erster, aktivem und kollaborativem Lernen an zweiter, Erleben von Kompetenz an dritter und akademischer Herausforderung an vierter Stelle. Die Ergebnisse können damit einen Weg aufzeigen, wie auch in ungewohnten Lehr-Lernsettings sukzessive ein geeignetes how to engage entwickelt werden kann, um student engagement zu fördern.

Tag Me If You Can: Insights into the Challenges of Supporting Unrestricted P2P News Tagging - Bäumer, Frederik Simon; Kersting, Joschka; Buff, Bianca; Geierhos, Michaela (Information and Software Technologies)
Peer-to-Peer news portals allow Internet users to write news articles and make them available online to interested readers. Despite the fact that authors are free in their choice of topics, there are a number of quality characteristics that an article must meet before it is published. In addition to meaningful titles, comprehensibly written texts and meaning- ful images, relevant tags are an important criteria for the quality of such news. In this case study, we discuss the challenges and common mistakes that Peer-to-Peer reporters face when tagging news and how incorrect information can be corrected through the orchestration of existing Natu- ral Language Processing services. Lastly, we use this illustrative example to give insight into the challenges of dealing with bottom-up taxonomies.

Transient Bodies, Bodies in Transition: An Introduction - Strauß, Sara; Schäfer-Althaus, Sarah (Transient Bodies in Anglophone Literature and Culture)

Ageing (Female) Bodies and Mortality in Eighteenth-Century Poetry - Strauß, Sara (Transient Bodies in Anglophone Literature and Culture)

Visualising Memory Loss and the Politics of Representation in Contemporary Portraiture - Strauß, Sara (Journal for the Study of British Cultures)

Einleitung - Meister, Dorothee; Mindt, Ilka (Mobile Medien im Schulkontext)

Digitale Elemente im Englischunterricht - Mindt, Ilka; Kaymak, Yasemin (Mobile Medien im Schulkontext)

Viele Wege führen nach Rom - Möglichkeiten und Modelle des Inverted-Classroom-Modells aus interdisziplinärer Sicht - Schmidt, Rebekka; Dietrich, Nico; Mindt, Ilka (Digitale Innovationen und Kompetenzen in der Lehramtsausbildung)

Mit digitalen Arbeitsformen das Lernen bereichern: zur Gestaltung sinnstiftender Präsenzphasen mit dem Inverted-Classroom-Modell - Mindt, Ilka; Schmidt, Rebekka; Beißwenger, Michael; Dietrich, Nico (Digitale Innovationen und Kompetenzen in der Lehramtsausbildung)

Student engagement im Inverted Classrom - Mindt, Ilka; Schmidt, Rebekka (Tagungsband zur Tagung Inverted Classroom and beyond 2020)

Kristin Bech and Ruth Möhlig-Falke, eds. Grammar – Discourse – Context: Grammar and Usage in Language Variation and Change. Berlin and Boston, MA: De Gruyter, 2019 - Mindt, Ilka

Posthuman Dystopia: Animal Surrealism and Permanent Crisis in Contemporary British Theatre - Tönnies, Merle; Voigts, Eckart (Journal of Contemporary Drama in English)

Bilingual education in monolingual contexts: a comparative perspective - Rumlich, Dominik (The Language Learning Journal)

Englischsprachige Jugendbücher innerhalb und außerhalb des Englischunterrichts – Young Adult Fiction als empirischer Gegenstand der Literaturdidaktik - Matz, Frauke; Rumlich, Dominik (KONTROVERS. Literaturdidaktik meets Literaturwissenschaft)

Die mündliche Prüfung in der Sekundarstufe II: Herausforderung und Chance für die Fremdsprachendidaktik - Matz, Frauke; Rogge, Michael; Rumlich, Dominik (Testen bildungssprachlicher Kompetenzen und akademischer Sprachkompetenzen – Zugänge für Schule und Hochschule)

Transient Bodies in Anglophone Literature and Culture

Aspect Phrase Extraction in Sentiment Analysis with Deep Learning - Kersting, Joschka; Geierhos, Michaela (Proceedings of the 12th International Conference on Agents and Artificial Intelligence (ICAART 2020) -- Special Session on Natural Language Processing in Artificial Intelligence (NLPinAI 2020))
This paper deals with aspect phrase extraction and classification in sentiment analysis. We summarize current approaches and datasets from the domain of aspect-based sentiment analysis. This domain detects sentiments expressed for individual aspects in unstructured text data. So far, mainly commercial user reviews for products or services such as restaurants were investigated. We here present our dataset consisting of German physician reviews, a sensitive and linguistically complex field. Furthermore, we describe the annotation process of a dataset for supervised learning with neural networks. Moreover, we introduce our model for extracting and classifying aspect phrases in one step, which obtains an F1-score of 80%. By applying it to a more complex domain, our approach and results outperform previous approaches.
Keywords: Deep Learning; Natural Language Processing; Aspect-based Sentiment Analysis

Detection of Privacy Disclosure in the Medical Domain: A Survey - Buff, Bianca; Kersting, Joschka; Geierhos, Michaela (Proceedings of the 9th International Conference on Pattern Recognition Applications and Methods (ICPRAM 2020))
When it comes to increased digitization in the health care domain, privacy is a relevant topic nowadays. This relates to patient data, electronic health records or physician reviews published online, for instance. There exist different approaches to the protection of individuals’ privacy, which focus on the anonymization and masking of personal information subsequent to their mining. In the medical domain in particular, measures to protect the privacy of patients are of high importance due to the amount of sensitive data that is involved (e.g. age, gender, illnesses, medication). While privacy breaches in structured data can be detected more easily, disclosure in written texts is more difficult to find automatically due to the unstructured nature of natural language. Therefore, we take a detailed look at existing research on areas related to privacy protection. Likewise, we review approaches to the automatic detection of privacy disclosure in different types of medical data. We provide a survey of several studies concerned with privacy breaches in the medical domain with a focus on Physician Review Websites (PRWs). Finally, we briefly develop implications and directions for further research.
Keywords: Identity Disclosure; Privacy Protection; Physician Review Website; De-Anonymization; Medical Domain

Neural Learning for Aspect Phrase Extraction and Classification in Sentiment Analysis - Kersting, Joschka; Geierhos, Michaela (Proceedings of the 33rd International Florida Artificial Intelligence Research Symposium (FLAIRS) Conference)

What Reviews in Local Online Labour Markets Reveal about the Performance of Multi-Service Providers - Kersting, Joschka; Geierhos, Michaela (Proceedings of the 9th International Conference on Pattern Recognition Applications and Methods)
This paper deals with online customer reviews of local multi-service providers. While many studies investigate product reviews and online labour markets with service providers delivering intangible products “over the wire”, we focus on websites where providers offer multiple distinct services that can be booked, paid and reviewed online but are performed locally offline. This type of service providers has so far been neglected in the literature. This paper analyses reviews and applies sentiment analysis. It aims to gain new insights into local multi-service providers’ performance. There is a broad literature range presented with regard to the topics addressed. The results show, among other things, that providers with good ratings continue to perform well over time. We find that many positive reviews seem to encourage sales. On average, quantitative star ratings and qualitative ratings in the form of review texts match. Further results are also achieved in this study.
Keywords: Customer Reviews; Sentiment Analysis; Online Labour Markets

Book review: Fictional Dialogue as Poiesis: Elizabeth Alsop’s Making Conversation in Modernist Fiction. - Mildorf, Jarmila (Diegesis)

Functions of Fictional Dialogue: Narratological and Historical Perspectives - Mildorf, Jarmila (La contribution du discours à la charactérisation des personnages biblique)

Music and Politics in the BBC Radio Adaptation of Alan Bennett’s The Madness of George III - Mildorf, Jarmila (Radio Art and Music: Culture, Aesthetics, Politics)

Radio Art and Music: An Introduction - Mildorf, Jarmila; Verhulst, Pim (Radio Art and Music: Culture, Aesthetics, Politics)

Book Review: Storytelling as Narrative Practice: Ethnographic Approaches to the Tales We Tell, Elizabeth A. Falconi, Kathryn E. Graber (Eds.), Brill, Leiden (2019) - Mildorf, Jarmila (Journal of Pragmatics)

Erzähllogik und Krankheitserfahrung: Siri Hustvedts The Shaking Woman - Mildorf, Jarmila (Jahrbuch Literatur und Medizin, vol.12)

Radio Art and Music: Culture, Aesthetics, Politics

Happiness Against All Odds: Incestuous Desires in John Ford’s ’Tis Pity She’s a Whore - Ehland, Christoph (Critical Survey)

Introduction: Cross-cultural Encounters and Expressions of Power in Middlebrow Literature and Culture, 1890-1940 and the present - Ehland, Christoph; Gohrisch, Jana (Imperial Middlebrow)

Beyond ‘the Miasma of London’: John Keats as Tourist - Ehland, Christoph (L'arte del ricardo: Romanticismo e cultural memory)

Rubens in England - Ehland, Christoph (Peter Paul Rubens und der Barock im Norden)

Informationskompetenz durch E-Learning? Durch Lernvideos nach Literatur suchen - Hahn, Charlotte Anna (die hochschullehre)
The aim of this study was to find out whether teaching how to search for literature would be more beneficial to students and teachers if done online through short videos rather than in person during course time. To find out whether online videos are more beneficial, two courses were asked to fill in questionnaires, one at the beginning and one at the end of the semester. One of the courses received the input online via videos and were given an exercise to put the newly learned skills to use, the other course served as a control group and learned how to search for literature during the course. The results show that while the difference between the two groups is not significant, the videos can still be regarded as being more beneficial than teaching the necessary skills during course time.
Keywords: E-Learning; information competence; literature; library; research

Cross-Cultural Encounters and Expressions of Power in Middlebrow Literature and Culture, 1890-1940 and the Present - Ehland, Christoph; Gohrisch, Jana (Imperial Middlebrow)

Inwiefern verbessert bilingualer Sachfachunterricht die Englischkompetenzen von Schülerinnen und Schülern? - Rumlich, Dominik (Die große Frage)

Freies Format 9: Nachwuchscafé - Juchem-Grundmann, Constanze; Matz, Frauke; Rumlich, Dominik (Sprachen lernen integriert: global, regional, lokal. Dokumentation zum 27. Kongress für Fremdsprachendidaktik der Deutschen Gesellschaft für Fremdsprachenforschung (DGFF). Jena, 27.-30. September 2017)

Kohärenz im Englischstudium für die Primarstufe: Das Lehr-Lern-Konzept des Wuppertaler Projekts EULE - Diehr, Bärbel; Becker, Annette; Breul, Carsten; Frisch, Stefanie; Kastens, Claudia; Rumlich, Dominik (Kohärenz in der Lehrerbildung)

Requirements Engineering in OTF-Computing - Bäumer, Frederik Simon; Geierhos, Michaela (encyclopedia.pub)
Keywords: OTF Computing; Natural Language Processing; Requirements Engineering

Natural Language Processing in OTF Computing: Challenges and the Need for Interactive Approaches - Bäumer, Frederik Simon; Kersting, Joschka; Geierhos, Michaela (Computers)
The vision of On-the-Fly (OTF) Computing is to compose and provide software services ad hoc, based on requirement descriptions in natural language. Since non-technical users write their software requirements themselves and in unrestricted natural language, deficits occur such as inaccuracy and incompleteness. These deficits are usually met by natural language processing methods, which have to face special challenges in OTF Computing because maximum automation is the goal. In this paper, we present current automatic approaches for solving inaccuracies and incompletenesses in natural language requirement descriptions and elaborate open challenges. In particular, we will discuss the necessity of domain-specific resources and show why, despite far-reaching automation, an intelligent and guided integration of end users into the compensation process is required. In this context, we present our idea of a chat bot that integrates users into the compensation process depending on the given circumstances.
Keywords: Inaccuracy Detection; Natural Language Software Requirements; Chat Bot

UPB-Annotate: Ein maßgeschneidertes Toolkit für historische Texte - Seemann, Nina; Merten, Marie-Luis (DHd 2019 Digital Humanities: multimedial & multimodal. Konferenzabstracts)

Potentielle Privatsphäreverletzungen aufdecken und automatisiert sichtbar machen - Bäumer, Frederik Simon; Buff, Bianca; Geierhos, Michaela (DHd 2019 Digital Humanities: multimedial & multimodal. Konferenzabstracts)

In Reviews We Trust: But Should We? Experiences with Physician Review Websites - Kersting, Joschka; Bäumer, Frederik Simon; Geierhos, Michaela (Proceedings of the 4th International Conference on Internet of Things, Big Data and Security)
The ability to openly evaluate products, locations and services is an achievement of the Web 2.0. It has never been easier to inform oneself about the quality of products or services and possible alternatives. Forming one’s own opinion based on the impressions of other people can lead to better experiences. However, this presupposes trust in one’s fellows as well as in the quality of the review platforms. In previous work on physician reviews and the corresponding websites, it was observed that there occurs faulty behavior by some reviewers and there were noteworthy differences in the technical implementation of the portals and in the efforts of site operators to maintain high quality reviews. These experiences raise new questions regarding what trust means on review platforms, how trust arises and how easily it can be destroyed.
Keywords: Trust; Physician Reviews; Network Analysis

Victorian Ideologies in Contemporary British Cultures

(New?) Masculinities in Nineteenth-Century Sensation Fiction and Contemporary Black British Fiction - Flotmann-Scholz, Christina; Lienen, Anna (Victorian Ideologies in Contemporary British Cultures)

Introduction - Flotmann-Scholz, Christina; Lienen, Anna (Victorian Ideologies in Contemporary British Cultures)

Victorian Ideologies in Contemporary British Cultures

How to Boost Customer Relationship Management via Web Mining Benefiting from the Glass Customer’s Openness - Bäumer, Frederik Simon; Buff, Bianca (Proceedings of the 8th International Conference on Data Science, Technology and Applications)

Requirements Engineering im OTF-Computing: Informationsextraktion und Unvollständigkeitskompensation mittels domänenspezifischer Wissensbasis - Friesen, Edwin

Aural Worldmaking: An Introduction - Mildorf, Jarmila (CounterText)

The Irrelevance of Relevance Theory for the Study of Generic Fiction - Mildorf, Jarmila (Style)

Can Sounds Narrate? Prosody in Sound Poetry Performance - Mildorf, Jarmila (CounterText)

Ressourcenorientiertes Schreiben. Tagebücher, Skizzen und Notate in der sozio-therapeutischen Praxis. Mit einem Exkurs zum Tagebuch der Trauer von Roland Barthes - Mildorf, Jarmila; Ketteler, Daniel (Jahrbuch Literatur und Medizin)

Why Poetry Matters: Defamiliarization and Perspective in Poetry - Mildorf, Jarmila (Lyrik und Medizin)

Narrating Selves and the Literary from the Bible to Social Media (Partial Answers)

Aural Worldmaking: Audionarratological Approaches to Sound and Narrative (CounterText)

Dance, Text and Philosophy in Gertrude Stein’s ‘One Dancing’ and Roger Scruton’s Perictione in Colophon - Mildorf, Jarmila (Germanisch-Romanische Monatsschrift)

Narratives of Vicarious Experience in Oral History Interviews with Craft Artists - Mildorf, Jarmila (Journal of Pragmatics)

Autobiography, the Literary and the Everyday in Paul Auster's 'Report from the Interior' - Mildorf, Jarmila (Partial Answers)

"Victorian Values in Nineteenth- and Twenty-First-Century Advertising and Consumer Practices" - Strauß, Sara (Victorian Ideologies in Contemporary British Cultures)

"Silvia Pellicer-Ortín, Julia Tofantšuk (eds.), Women on the Move. Body, Memory and Femininity in Present-Day Transnational Diasporic Writing" - Strauß, Sara (Miranda: Multidisciplinary Peer-Reviewed Journal on the English-Speaking World)

John Ford, ’Tis Pity She's a Whore - Ehland, Christoph (Handbook of English Renaissance Literature)

Loaded Language: Gun Rights and the Rhetoric of Post-Truth Politics. - Jende, Yvonne Kristin (Deception, Dishonesty, and Duplicity, Interdisziplinäre studentische Konferenz)

Narrating Selves from the Bible to Social Media: Introduction to the Forum - Hyvärinen, Matti; Hatavara, Mari; Mildorf, Jarmila (Partial Answers)

Mündliche Prüfungen (Der Fremdsprachliche Unterricht Englisch)

Bridging - Fremdsprache und Fachwissenschaft. Digital Learning Map - Mindt, Ilka

"Digital Humanitites: The Role of the Digital in English Philology". Sprachwissenschaftliche Sektion beim Anglistentag 2017 in Regensburg - Mindt, Ilka; Bartsch, Sabine (Anglistentag 2017 Regensburg. Proceedings)

Englischer Sprachwandel im Zeitalter von Digitalisierung und Innovation - Mindt, Ilka (Paderborner Unireden 148)

Digital Humanities: The Role of the Digital in English Philology - Bartsch, Sabine; Mindt, Ilka (Anglistentag 2017 Regensburg. Proceedings)

Section I: Digital Humanities: The Role of the Digital in English Philology - Bartsch, Sabine; Mindt, Ilka (Anglistentag 2017 Regensburg. Proceedings)

Englischer Sprachwandel im Zeitalter von Digitalisierung und Innovation - Mindt, Ilka

How to Deal with Inaccurate Service Descriptions in On-The-Fly Computing: Open Challenges - Bäumer, Frederik Simon; Geierhos, Michaela (Proceedings of the 23rd International Conference on Natural Language and Information Systems)
The vision of On-The-Fly Computing is an automatic composition of existing software services. Based on natural language software descriptions, end users will receive compositions tailored to their needs. For this reason, the quality of the initial software service description strongly determines whether a software composition really meets the expectations of end users. In this paper, we expose open NLP challenges needed to be faced for service composition in On-The-Fly Computing.
Keywords: Requirements Extraction; Temporal Reordering of Software Functions; Inaccuracy Compensation

Improving Classifiers for Semantic Annotation of Software Requirements with Elaborate Syntactic Structure - Kim, Yeongsu; Lee, Seungwoo; Dollmann, Markus; Geierhos, Michaela (International Journal of Advanced Science and Technology)
A user generally writes software requirements in ambiguous and incomplete form by using natural language; therefore, a software developer may have difficulty in clearly understanding what the meanings are. To solve this problem with automation, we propose a classifier for semantic annotation with manually pre-defined semantic categories. To improve our classifier, we carefully designed syntactic features extracted by constituency and dependency parsers. Even with a small dataset and a large number of classes, our proposed classifier records an accuracy of 0.75, which outperforms the previous model, REaCT.
Keywords: Software Engineering; Natural Language Processing; Semantic Annotation; Machine Learning; Feature Engineering; Syntactic Structure

Rezension von Ahrenholz, Hövelbrinks & Schmellentin (Hrsg; 2017): Fachunterricht und Sprache in schulischen Lehr-/Lernprozessen. Tübingen: Narr Franke Attempto. - Rumlich, Dominik (Fremdsprachen Lehren und Lernen)

Englischnoten und globale englische Sprachkompetenz in bilingualen Zweigen - Rumlich, Dominik (Zeitschrift für Erziehungswissenschaft)

Empirische Zugänge zum bilingualen Sachfachunterricht - Rumlich, Dominik (Zeitschrift für Erziehungswissenschaft)

Ein empirisch-quantitativer Blick auf „typische“ CLIL-Schüler(innen) und ihre Entwicklung - Rumlich, Dominik (Babylonia)

Current research on CLIL in the Netherlands: A discussion - Rumlich, Dominik (Dutch Journal of Applied Linguistics)

A national day of healing. Eine mündliche Prüfung als radio discussion gestalten - Matz, Frauke; Rumlich, Dominik (Der Fremdsprachliche Unterricht Englisch)

What Makes a Good Speaker of English? Sprechkompetenz mit mündlichen Prüfungen erfassen - Matz, Frauke; Rogge, Michael; Rumlich, Dominik (Der Fremdsprachliche Unterricht Englisch)

Sprechprüfungen: Kommentierte Auswahlbibliographie - Matz, Frauke; Rogge, Michael; Rumlich, Dominik (Der Fremdsprachliche Unterricht Englisch)

Bilingualer Sachfachunterricht - Fleckenstein, Johanna; Rumlich, Dominik; Möller, Jens (Englisch unterrichten)

Entwicklung eines Online-Workshops zum „Lernen-Lernen“: Individualisiertes Lernen mit Moodle - Rumlich, Dominik; Hellenbrand, Johannes; Leutner, Detlev (Flexibles Lernen mit digitalen Medien ermöglichen – Strategische Verankerung und Erprobungsfelder guter Praxis an der Universität Duisburg-Essen)

Freiraum zur individuellen Reflexion gemeinsamer Werte - Geierhos, Michaela (Integration und Toleranz)

Changing Uses of the City in Contemporary Black British Novels - Tönnies, Merle; Lienen, Anna (Resistance and the City. Negotiating Urban Identities: Race, Class, Gender)

Visualising Memory Loss and the Politics of Representation in Contemporary Portraiture - Strauß, Sara (Age Matters)

Identity Politics in George Lucas’ Star Wars. by John C. McDowell - Flotmann-Scholz, Christina (Cercles: Revue Pluridisciplinaire du Monde Anglophone)

Rate Your Physician: Findings from a Lithuanian Physician Rating Website - Bäumer, Frederik Simon; Kersting, Joschka; Kuršelis, Vytautas; Geierhos, Michaela (Communications in Computer and Information Science)
Physician review websites are known around the world. Patients review the subjectively experienced quality of medical services supplied to them and publish an overall rating on the Internet, where quantitative grades and qualitative texts come together. On the one hand, these new possibilities reduce the imbalance of power between health care providers and patients, but on the other hand, they can also damage the usually very intimate relationship between health care providers and patients. Review websites must meet these requirements with a high level of responsibility and service quality. In this paper, we look at the situation in Lithuania: Especially, we are interested in the available possibilities of evaluation and interaction, and the quality of a particular review website measured against the available data. We thereby identify quality weaknesses and lay the foundation for future research.
Keywords: Lithuanian physician review websites; Medical service ratings

NLP in OTF Computing: Current Approaches and Open Challenges - Bäumer, Frederik Simon; Geierhos, Michaela (Proceedings of the 24th International Conference on Information and Software Technologies (ICIST 2018))
On-The-Fly Computing is the vision of covering software needs of end users by fully-automatic compositions of existing software services. End users will receive so-called service compositions tailored to their very individual needs, based on natural language software descriptions. This everyday language may contain inaccuracies and incompleteness, which are well-known challenges in requirements engineering. In addition to existing approaches that try to automatically identify and correct these deficits, there are also new trends to involve users more in the elaboration and refinement process. In this paper, we present the relevant state of the art in the field of automated detection and compensation of multiple inaccuracies in natural language service descriptions and name open challenges needed to be tackled in NL-based software service composition.
Keywords: Inaccuracy detection; Natural language software requirements

Text Broom: A ML-based Tool to Detect and Highlight Privacy Breaches in Physician Reviews: An Insight into Our Current Work - Bäumer, Frederik Simon; Geierhos, Michaela (European Conference on Data Analysis 2018: Multidisciplinary Facets of Data Science - Book of Abstracts)